2019
DOI: 10.1001/jamanetworkopen.2019.10584
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Diagnostic Low-Dose Ionizing Radiation With Risk of Cancer Among Youths in South Korea

Abstract: This cohort study examines the association of low-dose radiation exposure in youths with risk of cancer using South Korean national health insurance data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 37 publications
0
80
3
2
Order By: Relevance
“…When deciding whether to use CT on children, the harmful effects that radiation may have on a growing body must be considered. Hong et al, in a study of 12,068,821 children aged 0 to 19 years, found a statistically significant increase in cancer in children exposed at least once to diagnostic low-dose ionizing radiation after adjusting for age and sex [29,30]. Based on our data, we do not recommend using CT for determining clinical recovery unless it is necessary to evaluate the status of pneumonia.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…When deciding whether to use CT on children, the harmful effects that radiation may have on a growing body must be considered. Hong et al, in a study of 12,068,821 children aged 0 to 19 years, found a statistically significant increase in cancer in children exposed at least once to diagnostic low-dose ionizing radiation after adjusting for age and sex [29,30]. Based on our data, we do not recommend using CT for determining clinical recovery unless it is necessary to evaluate the status of pneumonia.…”
Section: Discussionmentioning
confidence: 55%
“…Because of how many unknowns there were about the disease, particularly at the beginning of the COVID-19 outbreak, CT was frequently used in the clinical management and diagnosis of children in China. Notably, repeated use of CT can be harmful, particularly for children [29,30].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Typical chest imaging manifestations are reported to include multiple, patchy, sub-segmental or segmental ground glass density shadows in both lungs (1), though atypical findings are increasingly common. However, hereby we hope to reiterate that while CT radiation is associated with nonnegligible oncogenic risk (10,11), till now the role of CT for Covid-19 patients care remains poorly defined. Currently there is no effective anti-viral treatment or vaccine for 2019-nCoV (1).…”
mentioning
confidence: 88%
“…Similarly, X-rays are typically used to provide static images of body parts (such as teeth and bones), and are also used in industry to find defects in welds. But, ionizing radiations can be potentially harmful if not used correctly as these also include Alpha Particles, Beta Particles, Gamma Rays and X-Rays and Neutrons: which are emitted from naturally occurring radioactive materials (such as uranium, thorium, and radium) and other man-made radioactive elements and thus, need to be handled with utmost care (1)(2)(3)(4)(5)(6)(7)(8) .…”
Section: A Ionizing Radiationmentioning
confidence: 99%
“…Among the human beings, children and fetus are especially prone to radiation. Major sources of radiation exposure to this population group include diagnosis instruments used in hospitals, communication systems, dryers, etc 3,4 . This paper has been aimed to study the adverse effects of electromagnetic radiation on human health, especially mother, fetus and children.…”
Section: Introductionmentioning
confidence: 99%